Lietuvių kalbos būdvardžio semantinis valentingumas - Tekorienė, Dalija (Kalbotyra, 1983)
The author proceeds from the assumption that valency is to be studied at two levels, at least: the semantic level and the surface (syntactic) level. Analysis of valency at the semantic level is based on predication analysis and here three types of valency are distinguished: obligatory, nonobligatory and potential. Obligatory semantic valency is relatable to the number of participants in the situation, denoted by the predicator, which is obligatory and sufficient for the definition of the lexical meaning of the predicator. Non-obligatory valency is relatable to the number of circumstantial participants which are optional and non-obligatory for the definition of the meaning of the predicator. Potential valency reflects the fact that the number of obligatory participants in the intrinsic valencyset of certain predicators can fluctuate within the established limits.The majority of Lithuanian adjectives are intrinsically one-place predicators taking the possessor of the specified quality as their sole argument. There are, however, about 70 adjectives which are two-place predicators since they relate one entity to another. The author offers a semantic description of these adjectives, a further study of which would involve the analysis of the linguistic means used to express their obligatory valencyset at the surface level.Potential valency of Lithuanian bivalent adjectives is connected with the tendency of certain obligatory participants to acquire a very general meaning so that they cease to play any substantial role in the definition of the meaning of the adjective. However, they are always ready to take on a concrete meaning and thus become once again full-fledged intrinsic participants of the situation denoted by the adjective.